Literasi Digital Aman dan Etis Bagi Ibu PKK Kelurahan Pancoran Mas Depok - Ahmad Taufik; Irnawati; Utari Sekar Putri; Dieni Mulyasari (Perkumpulan Dosen Muslim Indonesia, 2026)
The rapid development of information technology has influenced various aspects of people's lives, including how they communicate, access information, and interact in the digital space. Social media and instant messaging applications have now become an important part of people's daily activities, including PKK mothers who play an active role in social activities and family empowerment. However, easy access to information in the digital era also creates new challenges in the form of low digital literacy, especially related to the ability to sort out correct, safe, and ethical information. Based on the results of observations and discussions with the PKK administrators of Pancoran Mas Depok Village, several main problems were identified that became the basis for the implementation of this activity, namely a low understanding of safe and ethical digital literacy, low ability to verify information (anti-hoax), low awareness of digital security cybersecurity such as digital fraud and data leaks, minimal digital mentoring and education. The digital literacy strengthening activities for partners have been implemented well and have had a positive impact on improving the competence of participants in the four main pillars of digital literacy: digital skills, digital security, digital culture, and digital ethics. Participants have become more understanding of how to use technology productively, safely, ethically, and are able to adapt to the increasingly evolving digital culture. This activity also successfully increased partners' readiness to utilize technology to support work effectiveness and organizational development. It is hoped that the acquired skills can be continuously applied and developed. Keywords: literacy, digital,technology